Physical condition of female students with different level of body mass deficiency - M.M. Kolokoltsev; S.S. Iermakov; M. Jagiello (Physical Education of Students)
Purpose : to study the features of morphofunctional and motor characteristics of female students with body mass deficiency and with normal body mass. Material : it was examined 17-21-year-old female students (n=1937). All students were in the main medical group according to the health condition and attended classes on discipline Physical culture. It was carried out the anthropometrical and physiometric examination of female students. Results : It was determined the low integrated criterion of physical fitness of female students with body mass deficiency. It was defined the dependence between the decrease in level of physical fitness and decrease in body mass of female students. It was determined reliable differences between the morphofunctional parameters and results of motor tests of female students with different body mass. Conclusions : The obtained data allow to correct educational process on physical training of students using integrative pedagogical methods and methods of training.